Spatial and temporal dynamics of European hake (Merluccius merluccius) in the North Sea. (13th August 2018) - Staby, Arved; Skjæraasen, Jon Egil; Geffen, Audrey J; Howell, Daniel
Abstract: Catches of European hake ( Merluccius merluccius ) in the North Sea have increased substantially during the last decade, even though there is no directed commercial fishery of hake in this area. We analysed the spatial distributions of hake in the northern the parts of its range, (where it is less well-studied), using ICES international bottom trawl survey data from 1997 to 2015. We examine length-frequency distributions for (i) distinct modes enabling the assignment of fish into categories which likely corresponded to the ages 1, 2, and 3+ and (ii) patterns of seasonal spatial distribution for the different groups. Age categories 1 and 2 fish were most abundant in the northern North Sea, and appear to remain in the North Sea until 2 years of age, when they move into deeper waters. Their distribution has expanded into the western-central North Sea in the last decade. Age category 3+ fish were most abundant in the northern and central North Sea during summer, indicating a seasonal influx of large individuals into this area likely associated with spawning activity. The distribution of these older fish has gradually expanded westward in both seasons.